Growing burden of sepsis-related mortality in northeastern Italy: a multiple causes of death analysis. Issue 1 (December 2016) - Fedeli, Ugo; Piccinni, Pasquale; Schievano, Elena; Saugo, Mario; Pellizzer, Giampietro
Abstract Background Few population-based data are available on mortality due to sepsis. The aim of the study was to estimate sepsis-related mortality rates and to assess the associated comorbidities. Methods From multiple causes of death data (MCOD) of the Veneto Region (northeastern Italy), all deaths with sepsis mentioned anywhere in the death certificate were retrieved for the period 2008–2013. Among these deaths the prevalence of common chronic comorbidities was investigated, as well as the distribution of the underlying cause of death (UCOD), the single disease selected from all condition mentioned in the certificate and usually tabulated in mortality statistics. Age-standardized mortality rates were computed for sepsis selected as the UCOD, and for sepsis mentioned anywhere in the certificate. Results Overall 16, 906 sepsis-related deaths were tracked. Sepsis was mentioned in 6.3 % of all regional deaths, increasing from 4.9 in 2008 to 7.7 % in 2013. Sepsis was the UCOD in 0.6 % of total deaths in 2008, and in 1.6 % in 2013. Age-standardized mortality rates increased by 45 % for all sepsis-related deaths, and by 140 % for sepsis as the UCOD. Sepsis was often reported in the presence of chronic comorbidities, especially neoplasms, diabetes, circulatory diseases, and dementia. Respiratory tract and intra-abdominal infections were the most frequently associated sites of infection. Conclusions MCOD analyses provide an estimate of the burden of sepsis-related mortality. MCOD data suggest an increasing importance attributed to sepsis by certifying physicians, but also a real increase in mortality rates, thus confirming trends reported in some other countries by analyses of hospital discharge records.